Femtosecond induced third-order optical nonlinearity in quasi 2D Ruddlesden–Popper perovskite film deciphered using Z-scan. Issue 22 (12th September 2022) - Mushtaq, Aamir; Pradhan, Bapi; Kushavah, Dushyant; Zhang, Yiyue; Naumenko, Denys; Amenitsch, Heinz; Hofkens, Johan; Pal, Suman Kalyan
Abstract : A quasi 2D Ruddlesden–Popper perovskite, (PEA)2 Cs4 Pb5 Br16 exhibits superior third-order nonlinear optical properties, which is promising for the development of ultrafast photonic devices. Abstract : Ruddlesden–Popper perovskite is a class of layered halide perovskite which gained much attention over the past few years in the field of photovoltaics. Herein, we have presented a compendious sketch of third-order nonlinear optical (NLO) properties of (PEA)2 Cs4 Pb5 Br16, a quasi-two-dimensional (2D) perovskite using femtosecond Z-scan technique at 800 nm. Our open aperture (OA) Z-scan measurements unveiled saturable absorption (SA) behaviour of the 2D perovskite with a nonlinear absorption coefficient of −13.83 cm GW −1, which is an order of magnitude higher than other 2D materials. Nonetheless, the self-defocusing effect has been demonstrated using a closed aperture (CA) Z-scan measurement. High nonlinear absorption coefficient and low saturation intensity (38.81 GW cm −2 ) infer that (PEA)2 Cs4 Pb5 Br16 perovskite film could be useful for ultrafast photonic applications.